2014
DOI: 10.3347/kjp.2014.52.3.311
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Trypanocidal Activity of Macela (Achyrocline satureioides) Extracts against Trypanosoma evansi

Abstract: The aim of this study was to verify the trypanocidal effectiveness of aqueous, methanolic, and ethanolic extracts of Achyrocline satureioides against Trypanosoma evansi in vitro. A. satureioides extracts, known as macela, were used on trypomastigotes at different concentrations (1, 5, 10, 50, 100, 500, and 1,000 µg/ml) and exposure times (0, 1, 3, 6, and 9 hr). A dose-dependent effect was observed when the 3 extracts were tested. The concentrations of 1, 5, and 10 µg/ml were not able to kill trypomastigotes un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…According to Rojas de Arias et al (1995), the ethanolic extract from A. satureioides at a concentration of 250 μg mL −1 showed 100% of lysis on bloodstream of Trypanosoma cruzi in vitro. It has also been reported in vitro trypanocidal effect of aqueous, ethanolic and methanolic extracts of A. satureioides against T. evansi (Baldissera et al, 2014a).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…According to Rojas de Arias et al (1995), the ethanolic extract from A. satureioides at a concentration of 250 μg mL −1 showed 100% of lysis on bloodstream of Trypanosoma cruzi in vitro. It has also been reported in vitro trypanocidal effect of aqueous, ethanolic and methanolic extracts of A. satureioides against T. evansi (Baldissera et al, 2014a).…”
Section: Discussionmentioning
confidence: 98%
“…The A. satureioides essential oil is composed by terpenes, substances formed by a great number of secondary organic metabolites (Langenheim, 2003). It is important to emphasize that terpernes and sesquiterpenes naturally or synthesized, had already proven in vitro trypanocidal effect against strains of T. cruzi (Baldissera et al, 2014a;Costa et al, 2011;Fernandes and Freitas, 2007). The β-Caryophyllene is a sesquiterpenes present in several plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Carmo et al (2015) [ 61 ] and Baldissera et al (2014) [ 62 ], the essential oil from the species Achyrocline satureioides (Lam.) DC.…”
Section: Essential Oils With Trypanocidal Activitymentioning
confidence: 99%
“…Treatment with essential oil of achyrocline satureioides in rats infected with Trypanosoma evansi revealed that essential oil did not eliminate the parasites from the bloodstream, but it reduced the number of trypanosomes, mainly by its nanoencapsulated form so, association of this natural product with a trypanocidal drug may enhance its curative effect (Baldissera et al, 2014a). Study on pre-clinical mouse model indicated that Heat shock protein 90 (Hsp90) from protozoan parasites may as a potential drug target of trypanosomiasis (Rochani et al, 2014).…”
Section: Alternative Approaches In Treatmentmentioning
confidence: 99%